(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The artice is devotcd to theoretic, methodobgical and practical aspects of creating psycho-didactic torns of brming the proessional idlentity of students-psychobgists during their studying The History of Psychobgy"